2005
DOI: 10.1162/089892905774597290
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Syntax Processing in Language and in Music: An ERP Study

Abstract: Abstract& The present study investigated simultaneous processing of language and music using visually presented sentences and auditorily presented chord sequences. Music-syntactically regular and irregular chord functions were presented synchronously with syntactically correct or incorrect words, or with words that had either a high or a low semantic cloze probability. Music-syntactically irregular chords elicited an early right anterior negativity (ERAN). Syntactically incorrect words elicited a left anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
271
4
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(318 citation statements)
references
References 42 publications
(76 reference statements)
33
271
4
5
Order By: Relevance
“…The MEG study of Maess et al (2001) and two fMRI studies by Koelsch et al (2005) and Tillmann et al (2003) additional sources in the right inferior frontal gyrus and inferior parietal lobule (Opitz et al, 2002;Park et al, 2002). In our discrete source analysis, the individual and grand average sources of the ERAN were located significantly more anterior than the MMN sources (see Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The MEG study of Maess et al (2001) and two fMRI studies by Koelsch et al (2005) and Tillmann et al (2003) additional sources in the right inferior frontal gyrus and inferior parietal lobule (Opitz et al, 2002;Park et al, 2002). In our discrete source analysis, the individual and grand average sources of the ERAN were located significantly more anterior than the MMN sources (see Fig.…”
Section: Discussionmentioning
confidence: 71%
“…The cognitive processes eliciting these brain responses are hence most likely different as well Koelsch et al, 2005;Koelsch et al, 2006;Leino et al, 2007). In particular, the extraction of rules dictating a hierarchical structure of musical events seem to require generators in the prefrontal cortex, whereas for the extraction of sequential music rules determining the frequency ratio between two consecutive sounds, the auditory cortex plays a primary role.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis further revealed that musicians showed significantly greater activity than nonmusicians in superior frontal, superior temporal, and lingual gyrus when confronted with incongruences. More importantly, the significant role of inferior frontal cortex for response inhibition (31) and for the identification of auditory pattern violations (32,33) has been repeatedly shown using several neuroimaging modalities (34) not only for linguistic (35) but also for musical stimuli (36). In addition, musicians show enhanced gray matter density (37) and enhanced connectivity of this region (38).…”
Section: Discussionmentioning
confidence: 88%
“…Musical syntax refers to the structural organization of musical events evolving over time and this organization is based on rules specific to the musical system. The comparison between the processing of syntactic structures in language and in music has raised the hypothesis of shared neural resources (see Patel et al, 1998;Patel, 2003;Koelsch et al, 2005). For R3, the two data sets on language and music thus suggest that the particular lesion pattern impairs sequential processing mechanisms that are necessary for syntax processing and that seem to be shared across these two domains.…”
Section: Discussionmentioning
confidence: 99%